Curriculum Innovation as an Epistemological Bridge in the Internationalization of Islamic Higher Education - Hanif, Ahmad Dzaky Nur; Merraphi, Alfidha Maulia (Universitas Muhammadiyah Yogyakarta, 2026)
The internationalization of Islamic higher education has become a strategic response to globalization, yet the transformation of its curriculum, as its core academic foundation, remains underexplored. While existing studies predominantly emphasize institutional cooperation and mobility programs, limited attention has been given to how curriculum innovation substantively mediates between global demands and Islamic epistemological identity. This study aims to analyze patterns of curriculum innovation that support the internationalization of Islamic Education study programs in higher education. This research employed a qualitative literature review using thematic analysis of peer-reviewed publications published between 2019 and 2024. Articles were selected using defined inclusion and exclusion criteria, focusing on curriculum development and internationalization in Islamic higher education contexts. The findings reveal five interrelated thematic dimensions: conceptual transformation of internationalization beyond mobility toward academic restructuring, integration of Islamic values within globally oriented and interdisciplinary curriculum design, urgency of adaptive, outcome-based, and technology-enhanced learning models, institutional strategies including international collaboration and digital engagement, and structural challenges such as epistemological dichotomy, limited resources, and uneven technological capacity. The study demonstrated that curriculum innovation functions as a strategic bridge aligning global competitiveness with Islamic value internalization. Sustainable internationalization, therefore, requires an integrative curriculum framework that preserves Islamic identity while enhancing global engagement and institutional capacity. This study advances a conceptual integrative framework positioning curriculum innovation as an epistemological mediator within Islamic higher education reform.